CONTEXTUAL TEACHING AND LEARNING APPROACHIN ENHANCING STUDENTS' SPEAKING SKILL(A CLASSROOM ACTION RESEARCH IN CLASS X-B SMA PURAGABAYA)A RESEARCH PAPER - Arief Setiawan, - (2008)
This research entitled Contextual Teaching and Learning Approach in Enhancing Students' Speaking Skill (A Classroom Action Research in Class X-B SMA Puragabaya) was conducted based on Classroom Action Research (CAR) which designed into three cycles and every cycle of which includes: planning, action, observation, and reflection. This research discusses the English learning process in the classroom using Contextual Teaching and Learning (CTL) approach to enhance the student's speaking skill, the students' behavior and responses toward the using of CTL approach in English lesson, and the students' speaking skill achievement as a result of using CTL approach in the instructional process. The writer used Contextual Teaching and Learning (CTL) approach as the problem solution. It is one of teaching and learning approach or concept which helps teachers and students to connect the lesson contents with a real life situation and motivate students to make a relationship between knowledge and its implementation in their life as family member, citizen, and employer. The data were gathered by conducting observation, questionnaire, interview, and by administering pre-test and post-test. The research result indicates that there were many positive enhancements toward the students' learning activities, learning behavior, and speaking skill. It was proven by the students' score and the class's average score increase in each cycle. Furthermore, the questionnaire results indicate that there were positive responses that CTL approach was effective both in arousing the students' motivation and their speaking skill.